2015
DOI: 10.2216/15-002.1
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin regulates antioxidative mechanisms in microalgaeChlamydomonas reinhardtii(Volvocales, Chlorophyceae)

Abstract: The role of melatonin (MLT) in micro-and macroalgae is the subject of continuous discussion. In eukaryotic unicellular organisms, the physiological role of MLT seems to differ from those of higher plants and mammals. Experimental data on the role of MLT in algae suggest that it acts mainly as an antioxidant. In the present study, the physiological role of MLT in phototrophic organisms was studied by measuring its effects on periodically controlled processes (cell division and HSP70B expression) as well as mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…The results are similar to those of a previous study. The addition of melatonin did not promote cell growth of C. reinhardtii under long day conditions . Notably, we observed that exogenous melatonin significantly enhanced the content of astaxanthin under nitrogen starvation and photoinduction by 2.25-fold compared to the control (Figure B).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The results are similar to those of a previous study. The addition of melatonin did not promote cell growth of C. reinhardtii under long day conditions . Notably, we observed that exogenous melatonin significantly enhanced the content of astaxanthin under nitrogen starvation and photoinduction by 2.25-fold compared to the control (Figure B).…”
Section: Discussionmentioning
confidence: 71%
“…The addition of melatonin did not promote cell growth of C. reinhardtii under long day conditions. 38 Notably, we observed that exogenous melatonin significantly enhanced the content of astaxanthin under nitrogen starvation and photoinduction by 2.25-fold compared to the control (Figure 1B). This indicates that melatonin enhanced the accumulation of astaxanthin in H. pluvialis in to stressful conditions.…”
Section: ■ Discussionmentioning
confidence: 77%
“…Further to higher plants, the effect of exogenously applied melatonin has also been studied in algae, which are a rich source of biopharmaceutical compounds, have high nutritional value, and represent major feedstock due to their high growth rate and high sugar contents (Bruhn et al 2011). For example, research with C. reinhardtii revealed that exogenous application of melatonin resulted in the suppression of FeSOD and MnSOD enzymatic antioxidants under conditions of photo-oxidative stress (Tal, Malkiel, Sinam, Harel & Haim 2015). In a more recent study, melatonin application in H. pluvialis led to increased astaxanthin biosynthesis and improved tolerance to limited nitrogen and high light conditions (Ding et al 2018).…”
Section: Algaementioning
confidence: 99%
“…To access and understand photoperiodism, the estimation of mRNA expression of heat shock protein HSP70B, Mn-superoxide dismutase MnSOD, Fe-superoxide dismutase FeSOD, and carotenoid have been done along with the cell division pattern, which is also associated with the circadian rhythm. 182 This melatonin was firstly used as an enhancer of astaxanthin biosynthesis in low-light and nitrogen-deprived conditions as a response to stressed conditions; the interaction of melatonin with the secondary messenger (nitric oxide and salicylic acid) was also observed along with the exploration of fatty acids. Fatty acids increase to the highest level of about 15.32 ± 0.04% of DCW in Haematococcus pluvialis .…”
Section: Comparison Between Different Strategies For Enhancing the Li...mentioning
confidence: 99%